The Perception of Brazilians on the Sustainable Development Goals (SDGs) and the Low-Carbon Economy - Rossana Parizotto Ribeiro; Ana Lígia Gil Espuny; Andrea Burmeister Morais Hermes; Elaine Marisa Andriolli (Centro Universitário Adventista de São Paulo, 2023)
Sustainable development, which aims to meet the needs of the present generation without compromising future generations' ability to meet their own needs, has become increasingly important as our planet faces escalating pollution and environmental challenges. The Low Carbon Economy (LCE) seeks to promote sustainable development by utilizing renewable energy sources to reduce environmental damage. In line with this objective, the United Nations launched the 2030 Agenda, comprising 17 Sustainable Development Goals (SDGs), which require collaborative efforts from civil society, governments, and businesses across 193 signatory countries to address global issues, particularly climate change. This research employs a quantitative and descriptive methodology, utilizing a survey conducted in the state of Rio Grande do Sul (RS), to assess the relevance of SDGs in the context of the Low Carbon Economy. The findings indicate strong correlations between the 17 SDGs and the Low Carbon Economy, as perceived by the respondents. Thus, the study confirms that the observed variables of the SDGs significantly influence the LCE, demonstrating the interdependence of all SDGs in shaping the Low Carbon Economy.